Ambivalence, Discontent, and Divides in Southeast Asia's Islamic Digital Realms: An Introduction. Issue 1 (13th July 2021) - Slama, Martin; Hoesterey, James Bourk
Abstract: This introductory article to the special issue Ambivalence, Discontent, and Divides in Southeast Asia's Islamic Digital Realms discusses the latest transformations in the field of Islam in Southeast Asia with a particular focus on digital media. It introduces the three key themes – ambivalence, discontent, divides – through which the special issue approaches contemporary socioreligious phenomena in Islamic Southeast Asia as they find their expressions online, often in close relation with offline dynamics. This approach allows this special issue to uncover the possibilities and predicaments afforded by engagement with digital and social media across Islamic Southeast Asia, understanding the latter as the locus of complex contestations, unanticipated affect, and poignant uncertainty. This introduction points to such un‐ or underexplored phenomena that considerably add to our understanding of religious and sociopolitical developments in contemporary Southeast Asia. The articles are introduced by highlighting how they contribute to our understanding of a broad mosaic of Islamic digital realms and how the latter have become sites of ambivalence, discontent, and divides. From Sufis to Salafis, masculinities to queer identities, and serious theologies to ludic critique, the case studies of this special issue devote special attention to the ambiguity, uneasiness, and division that marks Muslim engagement with digital domains across Southeast Asia.